ANALISIS NILAI HISTORIS SITUS WARISAN BUDAYA SENDHANG WICAKSANA DI DUKUH DENOKAN DESA POLOKARTO - Vita Astuti; Winda Dwi Lestari (Sabdasastra : Jurnal Pendidikan Bahasa Jawa, 2026)
The purpose of this research is to discover the historical values found in Sendhang Wicaksana, Denokan Hamlet. This study employs a qualitative descriptive method. There are three sources of data used in this research: informants, observation, and documents. The informant data sources consist of the caretaker, Javanese language teacher, and seventh-grade students. The observation data source is in the form of photographs of the sendhang’s building structure. The document data sources include interview transcripts, books, journal articles, websites, and the Javanese Language Merdeka Curriculum. The sampling technique used is purposive sampling. Data collection in this study was carried out through interviews, observation, and document analysis. The triangulation techniques used are data source triangulation and method triangulation. The technique used for data analysis is the Miles and Huberman theory, which consists of data reduction, data display, and drawing conclusions. Based on the analysis, it was found that the historical values of Sendhang Wicaksana are twofold: (1) changes and developments in the structure of the sendhang building, and (2) the development of the function/use of the sendhang.